A Novel Preoperative Planning Technique Using a Combination of CT Angiography and Three-Dimensional Printing for Complex Toe-to-Hand Reconstruction - Tan, Haitao; Yang, Keqin; Wei, Pingou; Zhang, Guodong; Dimitriou, Dimitris; Xu, Lin; Huang, Wenhua; Luo, Xiang (Journal of Reconstructive Microsurgery, 2015)
Background Microsurgical toe-to-hand transplantation is a reasonable salvage procedure after failed replantation, though no consensus exists on proper donor toe length for restoration of hand function and optimal donor flap needed for recipient site healing. The purpose of this study was to introduce a novel technique for preoperative planning in complicated toe-to-hand reconstruction and to assess feasibility in four cases.Methods Computed tomography (CT) angiography was used to map donor site vasculature, whereas CT data were used to create three-dimensional (3D) soft tissue and skeletal models for injured and uninjured hands. Based on the reformatted model (mirror of uninjured hand), soft tissue and finger skeleton models were generated using a 3D printer. An adhesive plaster model was placed on the donor site to determine osteotomy level and incision markings. The skeletal model was used to determine the length of the donor foot resection. Four complex amputation cases were included to illustrate clinical feasibility and early functional and cosmetic outcomes.Results In all four cases, thumb and fingers were reconstructed successfully and all flaps survived. No arterial or venous thrombosis or major donor morbidity were observed. Functional and cosmetic outcomes were satisfactory with similarly satisfactory static two-point discrimination, key pinch and grip strength, and Michigan Hand Outcomes Questionnaire scores.Conclusion This novel microsurgical toe-to-hand reconstruction methodology, as introduced in this study, showed promising functional and cosmetic outcomes. Application of this technique in complex hand injuries has the potential to increase surgical efficiency, minimize procedural morbidity, and improve reproducibility.
Keywords: microsurgery; toe-to-hand; transfer; computed tomography angiography; CT surgical planning